Can ultrasonography improve on radiographic assessment in osteoarthritis of the hands? A comparison between radiographic and ultrasonographic detected pathology. Issue 8 (23rd November 2007) - Keen, H I; Wakefield, R J; Grainger, A J; Hensor, E M A; Emery, P; Conaghan, P G
Abstract : Objectives: Ultrasonography (US) is used in rheumatology to assess small joints in inflammatory arthritis. Recently there has been some investigation into the utility of US in osteoarthritis (OA), however there has been little comparison of US to other imaging modalities in OA. This study aimed to compare the detection of osteophytosis and joint space narrowing (JSN) by US and conventional radiography (CR) in OA of the hand. Methods: Subjects with OA of the hand underwent US and CR examination of the small joints of both hands to identify osteophytosis and joint space narrowing. Results: 1106 joints of 37 patients were imaged with US and CR. US detected osteophytosis in 448 joints, compared to CR that detected osteophytosis in 228 joints (approximately 30% fewer joints). Where osteophytosis was detected by US but not CR, this was usually proximal to the joint line. Joint space narrowing was detected in 450 joints by US, but only 261 joints by CR. The distribution of US and CR detected osteoarthritis changes in this cohort was consistent with population studies of radiographic hand OA, although metacarpophalangeal (MCP) involvement was higher than might be expected Conclusions: US detected more osteophytosis and joint space narrowing than CR in OA of the hand. Involvement of MCP joints was more common than would be expected from population radiographic studies. The increased detection of OA structural pathology by US may make this a useful tool for hand OA research.